Antiarrhythmic properties of N-Deacetyllappaconitine Hydrochloride - S. A. Kryzhanovskii; M. S. Yunusov; I. B. Tsorin; V. V. Barchukov; E. I. Barchukova (LLC "Publisher OKI", 2022)
The aim of the investigation was the research of the N-deacetyllappaconitine hydrochloride antiarrhythmic properties. It was found that the studied substance was effective on the cardiac arrhythmias model caused by aconitine hydrochloride, but does not act on the models of calciume chlorideinduced arrhythmias and reperfusion ventricular fibrillation. The studied compound is less toxic than the comparison drug lappaconitine hydrobromide and acts in lower doses on the aconitine model of arrhythmias. N-Deacetyllappaconitine hydrochloride appears to be a Class I antiarrhythmic agent according to the Vaughan Williams classification.